Peran Public Relations dalam Corporate Social Responsibility (Csr) PT. Brodo Ganesha Indonesia - Siti Saptarini; sophia novita (Bandung Conference Series: Public Relations, 2022)
Abstract. The growth of the fashion industry is currently growing rapidly due to the increasing consumptive behavior of the community creates a fast fashion culture. With this behavior, it can increase the production of textile waste which will have a negative impact on the ecosystem for environmental sustainability in the long term. As a form of social responsibility PT. Brodo Ganesha Indonesia has a CSR program that cannot be separated from the role of Public Relations in it. This research aims to determind and analyze the role of Public Relations in implementation of CSR activities of The Brodo Lestari Project at PT. Brodo Ganesha Indonesia. The paradigm used is the Contructivism-Interpretivism paradigm. The research method used is a qualitative method with a case study approach, with the theory used to discuss this research is using the Theory of Public Relations Functions from Betrand R Canfield, and the source is determined based on purposive sampling techniques. The resource person of this research are Community Manager, Public Relations and the RnD team. With data collection techniques, namely observation, interviews, and documentation. Data analysis techniques are by data collection, data reduction, data presentation and drawing conclusions. In testing the validity of the data the author uses data triangulation. The results showed that the role of Public Relations PT. Brodo Ganesha Indonesia is very important in Sustainable Project activities as a form of public service by issuing responsible products to preserve the environment for the long term. CSR Activities of PT. Brodo Ganesha Indonesia is carried out over a long period of time or for the sake of preserving the environment around the company. Abstrak. Pertumbuhan industri fashion saat ini berkembang sangat pesat dikarenakan meningkatnya perilaku konsumtif masyarakat sehingga tercipta budaya fast fashion. Dengan perilaku tersebut dapat meningkatkan produksi limbah tekstil yang akan menimbulkan dampak buruk bagi ekosistem kelestarian lingkungan dalam jangka panjang. Sebagai bentuk tanggung jawab sosial PT. Brodo Ganesha Indonesia memiliki program CSR yang tak lepas dari peran Public Relations didalamnya. Penelitian ini bertujuan untuk mengetahui dan menganalisis mengenai peran Public Relations dalam pelaksanaan kegiatan CSR program Proyek Lestari Brodo di PT. Brodo Ganesha Indonesia. Paradigma yang dipakai adalah paradigma Contructivism-Interpretivism. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan studi kasus, dengan teori yang digunakan untuk membahas penelitian ini ialah menggunakan Teori Fungsi Public Relations dari Betrand R Canfield, dan narasumber ditentukan berdasarkan teknik penarikan purposive sampling. Narasumber dari penelitian ini adalah Community Manager, Public Relations, dan Tim RnD. Dengan teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi. Teknik analisis data yaitu dengan pengumpulan data, reduksi data, penyajian data dan penarik kesimpulan. Dalam uji keabsahan data penulis menggunakan triangulasi data. Hasil penelitian menunjukan bahwa peran Public Relations PT. Brodo Ganesha Indonesia sangat penting dalam aktivitas Proyek Lestari sebagai bentuk pengabdian terhadap publik dengan mengeluarkan produk yang bertanggung jawab demi menjaga kelestarian lingkungan untuk jangka panjang. Kegiatan CSR PT. Brodo Ganesha Indonesia ini dilaksanakan dalam kurun waktu yang lama atau berjangka panjang demi kelestarian lingkungan sekitar perususahaan.